2018
DOI: 10.1111/echo.14172
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fluid responsiveness by inferior vena cava diameter variation in post‐pneumonectomy patients

Abstract: Aim First, the inferior vena cava dilatation index (DIVC) was measured by ultrasound, and then the reliability of DIVC as an indicator to predict volume responsiveness in patients undergoing mechanical ventilation after pneumonectomy was evaluated. Methods Pulse indicator continuous cardiac output (Picco) as gold standard was performed to sedated mechanically ventilated post‐pneumonectomy patients in intensive care unit of Nanjing Thoracic Hospital from August 2014 to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…After the full-text review, 62 articles were excluded due to insufficient data ( n = 36), lack of 2-by-2 data ( n = 25), and not being original ( n = 1). Finally, 30 studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] comprising 1719 patients were included in this review ( Figure 1 ); detailed information about the eligible studies is shown in Table 1 . In cases of the IJV [ 29 , 36 , 42 ], FV (was not detected), and SCV [ 41 ], we were not able to conduct the meta-analysis due to an insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the full-text review, 62 articles were excluded due to insufficient data ( n = 36), lack of 2-by-2 data ( n = 25), and not being original ( n = 1). Finally, 30 studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] comprising 1719 patients were included in this review ( Figure 1 ); detailed information about the eligible studies is shown in Table 1 . In cases of the IJV [ 29 , 36 , 42 ], FV (was not detected), and SCV [ 41 ], we were not able to conduct the meta-analysis due to an insufficient number of studies.…”
Section: Resultsmentioning
confidence: 99%
“…All 30 eligible studies were summarized in Table 1 . Twenty-eight studies [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ] comprised the measurement of the IVC. Only three studies [ 29 , 36 , 42 ] comprised that of the IJV and one study [ 41 ] comprised that of the SCV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations